2020
DOI: 10.1186/s13046-020-01547-5
|View full text |Cite
|
Sign up to set email alerts
|

A SUMOylation-dependent HIF-1α/CLDN6 negative feedback mitigates hypoxia-induced breast cancer metastasis

Abstract: Background: We have previously described CLDN6 as a tumor suppressor gene in breast cancer. Here, a new finding is that CLDN6 was upregulated under hypoxia, a commonly recognized factor that promotes tumor metastasis. In this study, we aim to explain this confusing finding and delineate the role of CLDN6 in the breast cancer metastasis induced by hypoxia. Methods: RNAi and ChIP assays were used to confirm that CLDN6 is transcriptional regulated by HIF-1α. mRNA seq and KEGG analysis were performed to define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…After overexpression of CLDN6, negative feedback inhibited the expression of HIF-1α to decrease the metastasis of breast cancer ( 29 ). The downregulation of CLDN6 expression was positively correlated with lymph node metastasis in breast cancer ( 30 ).…”
Section: Expression and Regulation Mechanisms Of Cldn6 In Tumoursmentioning
confidence: 99%
“…After overexpression of CLDN6, negative feedback inhibited the expression of HIF-1α to decrease the metastasis of breast cancer ( 29 ). The downregulation of CLDN6 expression was positively correlated with lymph node metastasis in breast cancer ( 30 ).…”
Section: Expression and Regulation Mechanisms Of Cldn6 In Tumoursmentioning
confidence: 99%
“…The expression of CLDN6 is regulated by the degree of cell fusion and junctional maturation, as evidenced by the increase in expression with time and a high dependence upon plating density [8]. CLDN6 expression is also regulated by oxygen and estrogen, which are mediated by transcription factors such as HIF-1α [21,22] and Estrogen receptor α/β (Erα/β) [23,24], respectively. In the presence of tobacco smoke, CLDN6 is decreased in A549 and SAEC cells and mice lung tissues due to the interaction of HIF-1α and HIF-1α response element 1 (HRE1) at the CLDN6 promoter [21].…”
Section: Stimuli and Transcription Factorsmentioning
confidence: 99%
“…In the presence of tobacco smoke, CLDN6 is decreased in A549 and SAEC cells and mice lung tissues due to the interaction of HIF-1α and HIF-1α response element 1 (HRE1) at the CLDN6 promoter [21]. However, HIF-1α promotes CLDN6 transcription in hypoxic cultured breast cancer cells [22]. The two contrasting regulations of CLDN6 by HIF-1α may be related to the environment or tissue specificity, reflecting the complexity of protein regulation.…”
Section: Stimuli and Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…SENP1 may function by deSUMOylating related substrates. For example, a study found that SENP1 can deSUMOylate HIF-1α to enhance HIF-1α stabilization and ultimately promote breast cancer metastasis ( 66 ). Furthermore, SENP1 can deSUMOylate and regulate the protein activity and oncogenic function of the isomerase Pin1, which is an important regulator of cellular processes involving Pro-directed phosphorylation in breast cancer ( 67 ).…”
Section: Senp Family Members and Breast Cancermentioning
confidence: 99%